2011
DOI: 10.1111/j.1468-2494.2010.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

ESR study of photoinduced free radicals by visible light in hair and the effects of ascorbic acid (vitamin C)

Abstract: The ESR spectra of melanin's free radicals in natural black and red hair have been investigated. It is shown that the ESR spectrum of black hair is slightly asymmetric singlet with g=2.0037 and ΔH=0.5 mTl. The ESR spectrum of red hair with g=2.0053 differs from the spectrum of black hair. Using the method of saturation was shown that ESR spectrum of red hair represents a superposition of two signals: a singlet, relating to the black hair, and a triplet from red hair's pheomelanin. Under the influence of visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…It has to be noted that the g‐factor of each separate free radical is a constant parameter, but the g exp ‐factor, measured by the authors, defines the maximum position of the total ESR signal (Fig. ) and is dependent on the concentration ratio of eumelanin (eu) and pheomelanin (pheo) in the total spectrum …”
Section: Methodsmentioning
confidence: 99%
“…It has to be noted that the g‐factor of each separate free radical is a constant parameter, but the g exp ‐factor, measured by the authors, defines the maximum position of the total ESR signal (Fig. ) and is dependent on the concentration ratio of eumelanin (eu) and pheomelanin (pheo) in the total spectrum …”
Section: Methodsmentioning
confidence: 99%
“…In the same research we have also shown that ESR spectrum of the red hair is superposition of two ESR spectra-singlet of eumelanin and triplet of pheomelanin. According to ESR spectra observed in the study, it turned out that red hair of different donors contains different concentration of pheomelanin, [9] and that there are two different types of ESR spectra observed in human red hair: usually observed type I and rarely observed type II (Fig. 2).…”
Section: Resultsmentioning
confidence: 97%
“…[5][6][7] It was found out, that not only the UV irradiation, but also the visible light and IR can initiate generation of free radicals in the skin and hair. [8][9][10][11] Pheomelanin and its biological role in the human body have not been studied thoroughly yet. However, we know that this pigment has properties of prooxidant, which means that it is capable of generating harmful free radicals in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…3) and the spectral pattern was similar to that of previously reported pheomelanin-related radicals. 8,17 The low and high field signal intensities were markedly deferent (asymmetric pattern), suggesting that the radicals were immobilized. 8 The low and high field peak distance was approximately 3.2 mT.…”
mentioning
confidence: 99%
“…The characterization of pheomelaninrelated radicals is important as pheomelanin breaks down under light irradiation with the formation of superoxide. 17 Two-dimensional (2D) EPR image of MM and NP with DPPH (upper-panel) and without DPPH as a known radical concentration (lower-panel) is presented in Fig. 4a.…”
mentioning
confidence: 99%